Pengaruh diet rendah protein modifikasi terhadap keseimbangan nitrogen pada pasien penyakit ginjal kronik predialisis di RSU Dr. Soeradji Tirtonegoro - Agus Sunaryo; Ahmad Husein Asdie; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2007)
Background: Chronic kidney disease (CKD) is a decreasing function of kidney chronically, progressive, and irreversible. In this condition, one of the symptom found is uremia where gastrointestinal disturbance such as vomiting and anorexia occurred. This causes less nutrition intake, therefore careful diet is needed in attention. One of important aspect of diet procedures for CKD patients is eating management.Objective: To find out the influence of the modification of low protein diet intake towards nitrogen balance in predialysed CKD patients.Method: This was an experimental research using randomized controlled trial design.The subjects were predialysed CKD patients treated who fulfilled the following criteria: adult patients, obtained a low protein diet therapy, treated for at least two days, and willing to be examined. The treatments were a modification of low protein diet compare with a hospital standard of low protein diet.The twenty patients were devided into two groups namely a-ten-people treatment group and a-ten-people control.Result: The statistical test showed that there were no significant difference (p>0.05) in energy and protein intake, urea nitrogen appearance, and nitrogen balance between modification of low protein diet and the hospital standard of low protein diet in predialysed CKD patients.Conclusion: There were no significant difference in nitrogen balance between modification of low protein diet and the hospital standard of low protein diet in predialysed CKD patients.